Relative Prices and Inflation - Jackson, L (School of Management Working Papers, 1996)
Much recent writing about inflation has focussed on factors like menu costs which affect individual prices and are aggregated up to provide micro foundations for inflation. Using such an approach, Ball and Mankiw(l995) argue that the observed skewness of price change distributions is evidence of the importance of supply shocks in the inflation process. In this paper a more macro approach is adopted, and inflation is perceived as being the result of a process in which an underlying latent factor leads to change in prices in individual commodity markets. Using the US Producer Price Index data of Ball and Mankiw it is shown that there are systematic patterns in relative price changes during the inflation process, and that these patterns can explain both a changing variance and skewness in price changes. The model therefore provides a means of integrating a wide range of empirical observations about patterns in relative price change and a mechanism whereby policy actions could impact on the mean, standard deviation and skewness of price change distributions.